Target selection for FDA-approved medicines. Issue 7 (July 2015) - Kinch, Michael S.; Hoyer, Denton; Patridge, Eric; Plummer, Mark
Highlights Three target families dominate FDA-approved drugs, capturing almost half of all NMEs. The fraction of NMEs targeting unknown mechanisms has remained steady over time. Targeting novel mechanisms has increased progressively.